Kauniolide synthase is a P450 with unusual hydroxylation and cyclization-elimination activity - Qing Liu (Nature Portfolio, 2018)
Guaianolides are pharmaceutically interesting molecules. Here, the authors isolate the enzyme kauniolide synthase from feverfew, show that it converts constunolide into a guaianolide via an unusual mechanism of action, and reconstruct the full kauniolide biosynthesis pathway in host organisms.